Fetal anomaly screening programme. Issue 12 (December 2020) - Alt, Siobhan; McHugh, Annette; Permalloo, Nadia; Pandya, Pranav
Abstract: The Fetal Anomaly Screening Programme (FASP) is a national antenatal screening programme, responsible for two screening pathways: Down's syndrome, Edwards' syndrome, Patau's syndrome and 11 physical conditions at the 18–20 week scan. The core aim is to provide parents with information that supports their choices and values. In the last 19 years screening performances have improved significantly by defining a standardized approach, refining the tests offered, developing e-learning, supporting sonographers and laboratories with a quality assurance programme (Down's syndrome screening Quality Assurance Support Service) and auditing screening performance through the National Congenital Anomaly and Rare Diseases Registration Service. In 2021 FASP will implement non-invasive prenatal testing (NIPT) to screen for T21, T18 and T13 only. This will improve the choices offered to women and reduce the number of women having invasive prenatal diagnosis. In addition FASP is working with the National Institute for Health Research to potentially develop standards for evaluating specific fetal anomalies at 11–14 weeks.